Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/labinvest.3700346
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic rabbits with increased VEGF expression develop hemangiomas in the liver: a new model for Kasabach–Merritt syndrome

Abstract: Clinical studies have provided ample evidence that high (either systemic or local) levels of vascular endothelial growth factor (VEGF) are associated with several pathophysiological disorders, including hemangiomas. To investigate whether elevated VEGF expression could directly affect these disorders, we created a transgenic (Tg) rabbit model with increased hepatic expression of the human VEGF 165 transgene under the control of the human a-antitrypsin promoter. Tg rabbits exhibited marked hepatomegaly, with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Ultrathin sections were doubly stained with uranyl acetate and lead citrate and were observed under an JEM-100CX electron microscope (JEOL Ltd, Tokyo, Japan) as described previously. 32 …”
Section: Temmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrathin sections were doubly stained with uranyl acetate and lead citrate and were observed under an JEM-100CX electron microscope (JEOL Ltd, Tokyo, Japan) as described previously. 32 …”
Section: Temmentioning
confidence: 99%
“…32 A previous study showed that the ␣-1-antitrypsin promoter contained an element that was able to direct the expression of the transgene in the kidney in addition to the liver. 13 Three founders were obtained, but one founder died before breeding.…”
Section: Tg Rabbits Expressing Hvegfmentioning
confidence: 99%
“…52: [511][512][513][514][515][516] 2006) he rabbit is considered to be a valuable laboratory animal for research in teratology, immunology, microbiology, and medical and life sciences. In addition, many valuable mutants [1,2] including transgenic [3][4][5][6], have been established in the rabbit. Therefore, a need has been recognized for reliable methods to bank rabbit genetic resources efficiently in the form of cryopreserved spermatozoa.…”
mentioning
confidence: 99%
“…This is consistent with the decreased vascular branching in CD4C/N1 EC Tg liver, in contrast with the enhanced angiogenesis that would be expected if vascular endothelial growth factor levels were elevated. 61 Moreover, Tg rabbits overexpressing vascular endothelial growth factor in the liver under the regulation of the human ␣-antitrypsin promoter develop vascular malformations 62 but no superficial large vessels, as observed in CD4C/N1 EC Tg mice. Our search, however, revealed interesting candidates (MCP-1, MCP-5, FIII, FXIII-A, Jag1, and Egr-1) already known to be implicated in angiogenesis.…”
Section: The Pathogenesis Of the Liver Vascular Disease Of Cd4c/n1 Ecmentioning
confidence: 99%